Israel mathematical conference proceedings : complex analysis and dynamical systems VI - International Conference on Complex Analysis and Dynamical Systems in Honor of David Shoikhet on the Occasion of His Sixtieth Birthday (Nahariyah, Israel 19-24 May 2013); Agranovsky, Mark L.; Ben-Artzi, Matania; Galloway, Greg; Karp, Lavi; Khavinson, Dmitry; Reich, Simeon; Weinstein, Gilbert; Zalcman, Lawrence (Providence : American Mathematical Society, 2016)
This volume contains the proceedings of the Sixth International Conference on Complex Analysis and Dynamical Systems, held from May 19-24, 2013, in Nahariya, Israel, in honor of David Shoikhet's sixtieth birthday. The papers range over a wide variety of topics in complex analysis, quasiconformal mappings, and complex dynamics. Taken together, the articles provide the reader with a panorama of activity in these areas, drawn by a number of leading figures in the field. They testify to the continued vitality of the interplay between classical and modern analysis. The companion volume (Contemporary Mathematics, Volume 653) is devoted to partial differential equations, differential geometry, and radon transforms.
* Common boundary regular fixed points for homomorphic semigroups in strongly convex domains by M. Abate and F. Bracci* Univalence criteria depending on parameters and applications by D. Aharonov and U. Elias* Hausdorff operators in Hardy spaces on Cartan type domains in $\mathbb{C}^n$ by L. Aizenberg, E. Liflyand, and A. Vidras* On the expansive property of inner functions in weighted Hardy spaces by J. A. Ball and V. Bolotnikov Chordal* Loewner equation by A. del Monaco and P. Gumenyuk* On a lemma of Bergweiler by P. C. Fenton* Normal families of discrete open mappings with controlled $p$-module by A. Golberg, R. Salimov, and E. Sevost'yanov* Balls in the triangular ratio metric by S. Hokuni, R. Klen, Y. Li, and M. Vuorinen* Examples of reconstruction of homogeneous isolated hypersurface singularities from Their Milnor algebras by A. V. Isaev* On summation of the Taylor series of the function $1/(1-z)$ by the theta summation method by V. Katsnelson* Strengthened Grunsky and Milin inequalities by S. L. Krushkal* Quasiconformal mappings with replaced dilatation by R. Kuhnau* Universality limits involving orthogonal polynomials on a smooth closed contour by E. Levin and D. S. Lubinsky* Hele-Shaw flow with a time-dependent gap: The Schwarz function approach to the interior problem by K. Malaikah, T. V. Savina, and A. A. Nepomnyashchy* A Jordan approach to iteration theory for bounded symmetric domains by P. Mellon* Extreme points method and univalent harmonic mappings by Y. A. Muhanna and S. Ponnusamy* A weak ergodic theorem for infinite products of holomorphic mappings by S. Reich and A. J. Zaslavski* Circle packing and interpolation in Fock spaces by D. Stevenson and K. Zhu* Briancon-Skoda theorem for a quotient ring by A. Vidras and A. Yger* A survey on quasiconformal functions with application to the case of functions of a hypercomplex variable by F. Vlacci* On the Riemann-Hilbert problem for the Beltrami equations by A. Yefimushkin and V. Ryazanov
Includes bibliographical references.
Keywords: Functions of complex variables -- Congresses; Calculus of variations -- Congresses; Numerical analysis -- Congresses; Differential equations -- Congresses